2020
DOI: 10.1186/s12887-020-02154-1
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute malnutrition and its associated factors among children under-five years: a facility-based cross-sectional study

Abstract: Background Despite consistent efforts to enhance child nutrition, poor nutritional status of children continues to be a major public health problem in Nepal. This study identified the predictors of severe acute malnutrition (SAM) among children aged 6 to 59 months in the two districts of Nepal. Methods We used data from a cross-sectional study conducted among 6 to 59 months children admitted to the Outpatient Therapeutic Care Centers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 28 publications
10
37
1
Order By: Relevance
“…Several studies have found the association between SAM and low socio economic status [ 12 ], late initiation of breast feeding after one hour of the birth, non-exclusive breast feeding, birth interval less than two years [ 13 ], mother’s age at birth [ 10 ], maternal education [ 14 ], and family size [ 11 ]. Along with malnutrition among children and women, food insecurity remains an alarming problem in Nepal [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found the association between SAM and low socio economic status [ 12 ], late initiation of breast feeding after one hour of the birth, non-exclusive breast feeding, birth interval less than two years [ 13 ], mother’s age at birth [ 10 ], maternal education [ 14 ], and family size [ 11 ]. Along with malnutrition among children and women, food insecurity remains an alarming problem in Nepal [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the 2019 Global Hunger Index, Nepal ranks 73rd out of 117 qualifying countries and with a score of 20.8, Nepal suffers from a level of hunger that is serious [ 16 ]. Similarly, a study conducted in two Terai districts of Nepal (Jhapa and Bara) found that children from severely food insecure households were four times more likely to be severely malnourished [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, a stunted toddler will has a problem in gaining optimal physical and cognitive growth. 19 In this case, anthropometrics measurement revealed the length of age was below -3 SD of WHO Z-score curve. Its consequence of chronic malnutrition was accompanied by chronic infection.…”
Section: Discussionmentioning
confidence: 75%
“…The proportion of females (51.5%) among the admitted children was higher. These two features are very important and evidence shows that severe acute malnutrition is very high among females and among the younger age group of children 19 and they should be given priority in programs for tackling malnutrition. Similar findings were reported in others studies where a greater number of females were admitted in NRCs as compared to males.…”
Section: Discussionmentioning
confidence: 99%
“…9 Other studies have reported mortality varying between 0.4% and 3.5% in different States which is less than other countries. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] This compares favourably with the national and international standards of care (<10% child deaths). 11,27 This is a significant finding as the primary objective of facility-based management of SAM is to reduce fatality rates.…”
Section: Discussionmentioning
confidence: 99%